Distribution of Lichen Flora at different altitudes of Gunung Machincang, Langkawi Islands, Malaysia - Zulkifly, S.; Kim, Y.S.; Majid, M.A.; Merican, Amir Feisal (Penerbit Universiti Kebangsaan Malaysia, 2011)
Lichen samples were collected from Gunung Machincang, Langkawi Islands based on an alternation of altitudes, which are 0, 300 and above 600 m. Morphological identification resulted in 15 genera of microlichens (crustose) and five genera of macrolichens (foliose) and they fall under 14 families. As the altitude increases, the number of foliose type of lichen also increased. The common microlichens obtained were from the Family of Graphidaceae and can be found from the sea level right up to the peak of Gunung Machincang. The most common crustose lichens found were Heterodermia sp., while Eugenia sp. is the most common tree habitat for lichens in Gunung Machincang, Langkawi Islands. This study represents the first record of lichens in Gunung Machincang, Langkawi Islands, Malaysia.